SPECIFICS OF MORPHOLOGICAL STRUCTURE OF THE SKIN IN ISCHEMIC TROPHIC ULCERS IN VIEW OF MACROPHAGE ACTIVITY OF INFLAMMATORY INFILTRATE - Umerov, E.E. (World of Medicine and Biology, 2013)
Based on the undertaken immunohistochemical study of the skin biopsies of the patients with trophic ulcers, there have been identified two groups of macrophages involved in the development of alterative inflammatory processes, depending on their functional activity that reliably and dramatically exceeded control group parameters. This allowed for the first time to calculate the index of macrophage activity, which indicates a decline in the phagocytic function of macrophages that can be a predictor of delayed reparative processes in the healing of trophic ulcers.